DNA‐repair status should be assessed in treatment‐emergent neuroendocrine prostate cancer before platinum‐based therapy. Issue 4 (17th January 2022) - Zhu, Shimiao; Zhang, Zheng; Zhang, Hui; Liu, Zihao; Liu, Min; Liu, Qing; Zang, Li; Wang, Lili; Ji, Junpeng; Wu, Bo; Sun, Libin; Zhang, Zhenting; et al.
Abstract: Objectives: This study sought to provide contemporary data from a multi‐institution with respect to DNA‐repair genes (DRGs) status and its impact on effects of platinum‐based chemotherapy in treatment‐emergent neuroendocrine prostate cancer (t‐NEPC), for which little data exist. Patients and Methods: All patients were retrospectively collected with eligible biopsied tissues for targeted next generation sequencing (NGS). The main outcomes were radiologic progression‐free survival and overall survival according to Response Evaluation Criteria in Solid Tumors, version 1.1. Results: Among the 43 NEPC patients, 13/43 (30%) harbored homozygous deletions, deleterious mutations, or both in DRGs. Eleven patients (11/13, 85%) with DRGs aberrations had effective response, including 7 patients with BRCA1/2 defects and 2 with mismatch repair‐deficient caused by MSH2 alterations. While significantly fewer responders (30%) were detected in patients without DRGs aberrations (odds ratio = 12.83, p = 0.003). Compared with patients without genomic DRGs aberrations, the hazard ratio (HR) for radiologic progression in those with DRGs defects was 0.42 (95% confidence interval [CI]: 0.19–0.93), and the HR for death was 0.65 (95% CI: 0.24–1.72). The most common adverse event of Grade 3 or 4 was anemia, as noted in 7 patients (16%). Conclusion: The DRGs status is therapeutically meaningful in t‐NEPC. Given the potential responses to platinum‐based chemotherapy, our findings support the clinical use of NGS in t‐NEPC patients to identify DRGs aberrations.